Antimicrobial activities and enhancers of DNA gyrase inhibitors from manure compost actinomycetes / Anis Low Muhammad Low - Muhammad Low, Anis Low (Institute of Graduate Studies, UiTM, 2016)
Actinomycetes are invaluable sources of bioactive microbial compounds and have been the central of novel drug research as they continuously contribute to the pharmaceutical industry. The traditional perception of actinomycetes being soil bound has currently changed with evidence demonstrating their colonization in unique microenvironment. Through evolution and environmental adaptation, development of unusual metabolic activities has resulted in a variety of anti-infective agents from these bacteria. Nevertheless, the discovery of actinomycetes and its bioactive secondary metabolites from manure compost materials remained understudied. This research was therefore undertaken with the aim of isolating and characterizing the diversity of actinomycetes from manure composts, identifying morphologically distinct isolates, screening isolates for potential antimicrobial activities and bioactive compounds which act as enhancers for DNA gyrase inhibitor as well as elucidating compound(s) responsible for these activities. A collection of 191 actinomycete isolates were recovered from five types of manure composts collected around Selangor, Malaysia. The highest recovery was observed on SCNA medium at 30ºC. The combination of micromorphological characteristics and 16S rRNA sequence analysis revealed considerable actinomycete diversity which covers 12 genera within nine families…